2009
DOI: 10.1111/j.1365-2834.2009.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the nurses’ role in healthcare delivery through strategic management: recognizing its importance or not?

Abstract: Nurse Managers could play a greater role in enhancing healthcare delivery if an understanding of, and acceptance of the importance of strategy in health care delivery was promoted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…They further state ‘developing and managing strategy is a critical success factor for healthcare managers’ (Carney & Crossan, :655). Interestingly in , Carney examined the use and influence of strategy within nursing and midwifery by exploring databases using the key term ‘strategy’ in the title. The authors revealed that only 10% of papers made reference to this.…”
Section: An Outline Of Patterns and Trends In Papers Published The Jomentioning
confidence: 99%
“…They further state ‘developing and managing strategy is a critical success factor for healthcare managers’ (Carney & Crossan, :655). Interestingly in , Carney examined the use and influence of strategy within nursing and midwifery by exploring databases using the key term ‘strategy’ in the title. The authors revealed that only 10% of papers made reference to this.…”
Section: An Outline Of Patterns and Trends In Papers Published The Jomentioning
confidence: 99%
“…those values traditionally associated with nursing and those values traditionally linked with management) (Hewison & Stanton 2002, Crossan 2008; the need to meet the developmental needs of nurse managers in support of their middle management role (Hewison & Griffiths 2004, Clarke et al 2012; and the need to empower nurse managers and other middle managers to fulfil the role effectively. Carney (2009) indicates that there is a lack of awareness among nurse managers in relation to the strategic management of their organisations and suggests that nurse managers need to further develop their understanding and knowledge of the strategic management process and identify ways to influence their organisational strategy. However, this can only happen if nurse managers are given more support from the executive level of the organisation and recognition that the provision of enhanced education in strategic management is necessary if nurse managers are to play a meaningful role in the strategic development of health care.…”
Section: The Role Of the Nurse In Strategic Managementmentioning
confidence: 99%
“…Much of the literature examining nurses' experience of change has focused on middle-level staff (Carney, 2009). For example their role as 'knowledge brokers' has been investigated revealing that ward managers/ward sisters in particular contribute to the organisation of hospitals and have some strategic influence (Burgess and Currie, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However less attention has been given to nurses working at a strategic level with regard to organizational change (Crossan, 2003). It has been suggested that there is a lack of awareness among nurse managers of strategic management concerns in organizations (Carney, 2009), and that understanding and knowledge in this area needs further development (Crossan, 2003). If strategic management is a set of managerial decisions and actions of an organization which facilitate competitive advantage and longterm superior performance over other organizations (Kong, 2008), then the extent to which nurses in acute trusts are engaged in this activity requires investigation.…”
Section: Introductionmentioning
confidence: 99%